2016
DOI: 10.1038/cr.2016.156
|View full text |Cite
|
Sign up to set email alerts
|

Long-term propagation of tree shrew spermatogonial stem cells in culture and successful generation of transgenic offspring

Abstract: Tree shrews have a close relationship to primates and have many advantages over rodents in biomedical research. However, the lack of gene manipulation methods has hindered the wider use of this animal. Spermatogonial stem cells (SSCs) have been successfully expanded in culture to permit sophisticated gene editing in the mouse and rat. Here, we describe a culture system for the long-term expansion of tree shrew SSCs without the loss of stem cell properties. In our study, thymus cell antigen 1 was used to enrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
63
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 68 publications
0
63
0
2
Order By: Relevance
“…Inhibition of GSK3 leads to the activation of the Wnt/β‐catenin signaling pathway. As recently reported in tree shrew (Li et al, ), Wnt/β‐catenin signaling pathway is involved in the maintenance of undifferentiated spermatogonia from adult testes during the early stage of in vitro culture. Moreover, Wnt signaling also supports regulation of the character as stem cells of mouse spermatogonial stem/progenitor cells (Golestaneh et al, ) and promotes the proliferation of SSC progenitor cells (Takase & Nusse, ).…”
Section: Discussionmentioning
confidence: 58%
“…Inhibition of GSK3 leads to the activation of the Wnt/β‐catenin signaling pathway. As recently reported in tree shrew (Li et al, ), Wnt/β‐catenin signaling pathway is involved in the maintenance of undifferentiated spermatogonia from adult testes during the early stage of in vitro culture. Moreover, Wnt signaling also supports regulation of the character as stem cells of mouse spermatogonial stem/progenitor cells (Golestaneh et al, ) and promotes the proliferation of SSC progenitor cells (Takase & Nusse, ).…”
Section: Discussionmentioning
confidence: 58%
“…As for SSCs, although a large number of ncRNAs have been screened as potential regulatory molecules for SSC self‐renewal using high‐throughput RNA sequencing and bioinformatics approaches, only a small portion of them have been validated and functionally characterized using biological experiment to uncover roles in SSCs self‐renewal, particularly lncRNAs, piRNA, and circRNAs (K. Hu et al, ; Li et al, ; X. Li, Ao, et al, ), thus there is an urgent need to reveal more ncRNAs associated with SSC self‐renewal to elucidate the molecular mechanisms underlying SSC self‐renewal. Encouragingly, great improvements of technologies have been recently made on isolation, characterization, in vitro culture, and in vivo transplantation of SSCs will provide us a robust research platform to explore the function of ncRNAs in SSC self‐renewal (X. Li, Ao, et al, ; Mulder et al, ; Takashima & Shinohara, ; Zhang, Sun, & Zou, ). Remarkably, common genome editing techniques such as TALEN and CRISPR–Cas offer a rapid, efficient, and accurate genome engineering platform for functional characterization of putative ncRNAs in the context of established various models both in vitro and in vivo (Sato et al, ; Tang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research, which established EGFP-tagged transgenic tree shrews following spermatogonial stem cell (SSC) transplantation, provided a good approach for the generation of multiple human disease models using the tree shrew by gene editing manipulation ( Li et al, 2017 ). Although BCC was not observed in DMBA/TPA combination treated wild-type mice ( Indra et al, 2007 ), it has been successfully generated in Ptch flox/flox CD4Cre +/- mice ( Uhmann et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The recent elucidation of the genome of Tupaia belangeri chinensis confirmed the close genomic relationship between Tupaia belangeri and primates ( Fan et al, 2013 ). As a favorable animal model, the tree shrew has been used for many human disease studies, including research on depression ( Fuchs, 2005 ; Wang et al, 2011 ; 2012 ; 2013 ), drug addiction ( Sun et al, 2012 ; Zhang et al, 2011 ), virus infection ( Amako et al, 2010 ; Yan et al, 1996 ; Yang et al, 2005 ), bacterial infection ( Li et al, 2012 ), breast cancer ( Elliot et al, 1966 ; Ge et al, 2016 ; He et al, 2016 ; Xia et al, 2012 ), glioblastoma ( Tong et al, 2017 ), thrombosis ( Endo et al, 1997 ), metabolic diseases ( Wu et al, 2013 ; 2016 ; Zhang et al, 2015 ; 2016 ), stem spermatogonium transgenics ( Li et al, 2017 ), and myopia ( Norton et al, 2006 ). Recently, pharmacological research through drug target prediction and genomic and transcriptomic scale analysis has shown that more than half of the drug target proteins identified from the tree shrew genome demonstrate higher similarity to human targets than that of the mouse, as validated by the constitutive expression of proteinase-activated receptors ( Zhao et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%